Kedudukan Cucu Sebagai Ahli Waris Pengganti Dalam Hukum Waris Islam (Studi Kasus Nomor: 0013/PDT.P/2015/PA.DPS) - Ida Ayu Adi Iin Yuliandari; I Ketut Sukadana; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2020)
Abstract—Of all the current laws, inheritance law has a very important role and even determines and reflects the kinship system that has prevailed in that society. Lately there have been many disputes arising from the death of the heirs before the heirs. The case is sought out by forming a substitute heir concept. Legal issues regarding substitution of heirs are one of the concepts of renewal in the Compilation of Islamic Law. The concept of substitute heirs aiming to find a sense of justice for heirs. The formulation of the problem raised is (1) What is the position grandchildren as substitut heeirs in Inslamic intheritance law system according to the Compilation of Islamic Law, (2) How is the judge's judgment on the position of grandchildren as substitute heirs in the Determination of Denpasar Religious Court Number 0013/Pdt.P/2015/PA.Dps. In this research using normative legal research, namely in the study systematically process library materials and related decision files. In this study it can be concluded that the position of grandchildren as substitute heirs in the Islamic inheritance system according to the Compilation of Islamic Law based on the Determination of the Denpasar Religious Court Number 0013/Pdt./2015/PA.Dps that the grandchildren can replace the position of their parents as heirs, because based on Article 185 paragraph (1) Compilation of Islamic Law, a person can inherit because the replacement of the place is the person who is replaced musthave passed away earlier than the heir.